Application of wheat straw-derived amendments combined with sulfate increases soil microbial diversity, reduces soil cadmium mobility and cadmium accumulation in rice - Xianlin Ke; Songyan Li; Guoxi Wang; Xiaosong Yang; Mingming Tao; Yanhua Qiu; Yifei Li; Yu Liu; Lijuan Huang; Zhengyi Hu (Ecotoxicology and Environmental Safety)
Cadmium (Cd) accumulation in rice grains poses severe health risks. Conventional straw amendments exhibit inconsistent efficacy, likely because of variations in amendment types and soil sulfur deficiency. The pot experiment was evaluated in a Cd-contaminated paddy soil (3.18 mg Cd kg−1) to compare three treatments (1.0 % w/w) sources: WS (wheat straw), CW (wheat straw compost), and BW (wheat straw biochar) without or with sodium sulfate fertilization (30 mg sulfur kg−1). This experiment aimed to evaluate the Cd mobility, microbial diversity, and Cd accumulation in rice tissues. All treatments resulted in reduced Cd accumulation in brown rice at the maturity stage by 3 % (WS), 26 % (CW), and 60 % (BW), whereas sulfate co-application enhanced this reduction to 30 % (WS+S), 38 % (CW+S), and 66 % (BW+S). This could be attributed to decrease in soil Cd availability (17 %, 37 %, and 41 % for WS+S, CW+S, and BW+S, respectively, at the maturity stage), inhibition of Cd uptake by root iron plaque (-0.01 to −0.05), and decrease of Cd translocation in rice tissues (particularly phloem transfer). Microbial analysis revealed that biochar and compost preferentially increased bacterial alpha diversity and shifted microbial composition irrespective of sulfate supply, especially at the tillering and booting stages. Specifically, biochar and compost reduced Firmicutes (positively related to exchangeable Cd, P ≤ 0.01), and increased Bacteroidota and Proteobacteria (negatively related to exchangeable Cd, P ≤ 0.01) at these stages. These findings demonstrate that co-application of wheat straw biochar and sulfate offers a solution for remediating Cd-contaminated paddy soils while considering soil ecosystem health.